The Effect of Adding Chicken Wire as Steel Fibre on Some Properties of Polymer Concrete (Iraqi Journal of Civil Engineering, 2010)
AbstractThis research includes the study of the effect of adding steel fibres resulting from cutting chicken wire (which is available in Iraqi markets now) as fibres added to the polymer concrete. These fibres were added with percentages of concrete volumes. These percentages were (0.5%) and (1%). Reference concrete mix was also made for comparative reasons. From the results, it can be noted that the increasing of compressive strength of SFPC1 comparing with RPC at 28 days equal to 9.90%, whereas the increasing of compressive strength of SFPC2 comparing with RPC at 28 days is equal to 15.48%. The increasing of splitting strength of SFPC1 comparing with RPC at 28 days equal to 15.50%, whereas the increasing of SFPC2 comparing with RPC at 28 days is equal to 21.40%. The increasing of flexural strength of SFPC1 comparing with RPC at 28 days equal to 10.80%, whereas the increasing of SFPC2 comparing with RPC at 28 days is equal to 20.63%.Results proved that adding of steel fibres with these percentages lead to improvements in compressive strength, splitting strength and flexural strength of concretes containing steel fibres, but the improvement in flexural strength appeared more clearly. Results proved also an increasing in densities of fibre concrete samples according to these made of reference mix.